PS-B04-8: YM750, AN ACAT1 INHIBITOR, REDUCES ALDOSTERONE SECRETION BY DECREASING ADRENAL CYP11B2 EXPRESSION. (January 2023) - Shimada, Hiroki; Otsubo, Yuri; Hata, Shuko; Sato, Ikuko; Yamazaki, Yuto; Yokoyama, Atsushi; Suagwara, Akira; Nakamura, Yasuhiro
Abstract : Primary aldosteronism (PA) is a refractory hypertension that accounts for approximately 5%-10% of hypertensive patients. aldosterone-producing adenomas and idiopathic hyperaldosteronism are known causes of PA. In aldosterone-producing adenomas, depolarization due to somatic mutations of ion channels in adrenocortical cells is considered the cause of aldosterone oversecretion. Recently, there have been reports on the expression of various cholesterol-metabolizing enzymes in aldosterone-producing adenomas, suggesting that intracellular cholesterol metabolism is very important for aldosterone secretion. We present here the possibility that an inhibitor of Acetyl-CoA acetyltransferase (ACAT1), an enzyme that converts cholesterol to cholesteryl esters, may inhibit aldosterone secretion by depolarization in adrenal cells. Potassium chloride and YM750, an ACAT1 inhibitor, were added to human adrenocortical carcinoma, H295R cells. Then, we measured aldosterone synthase gene, CYP11B2 mRNA expression level. As a result, the expression level of CYP11B2 decreased. Both NURR1 and NGFIB mRNA expression levels also decreased. Additionally, aldosterone production was also measured and found to be significantly decreased in the YM750 added group. Next, angiotensin II was added and the inhibitory effect of YM750 was examined. The results showed that CYP11B2 expression was not decreased. This indicates that YM750 decreased the induction of CYP11B2 expression in a potassium chloride-induced stimulus-specific manner. The experimental results suggest that YM750 specifically inhibits CYP11B2 gene expression by cell depolarization and suppresses aldosterone secretion. However, there are few reports of cholesterol metabolism affecting CYP11B2 gene expression. In this study, we found that intracellular cholesterol metabolism may affect CYP11B2 gene expression. We plan to investigate the relationship between ACAT inhibition and CYP11B2 gene expression in detail mechanisms in the future.